THE IMPACT OF DIGITALIZATION ON COMPETITIVENESS OF BULGARIAN AGRICULTURE - Teodora STOEVA; Violeta DIRIMANOVA; Petar BORISOV (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Digitization is the key topic of our time. The impact of new technologies has a huge potential especially in Bulgarian agriculture. In the conditions of the COVID-19 and financial crisis, Bulgarian agriculture faces a difficult choice – farmers have to make serious investments in digitalization in order to be able to meet the European requirements related to food quality and environmental protection. The purpose of this article is to present and analyze the impact of digitalization on competitiveness of agricultural sector in Bulgaria, and to outline the direction related to the proper use of technologies for the rapid development of Bulgarian agriculture. The study is based on the documentation method which made of laws and regulations in the sphere of agriculture, as well as specific legislation related to digitalization. In the conditions of the COVID-pandemic which has accelerated the process of digitization and support for farmers who introduce digital technologies, innovative technologies for production and organization in agriculture, in order to increase the competitiveness of the agricultural sector in Bulgaria.